Inter-organizational competition in humanitarian governance - Corsini, C (2024)
In a world where humanitarian crises are increasing in severity and frequency, the humanitarian system is often described as a ‘competitive marketplace,’ an international regime densely populated by diverse actors – UN organizations, the Red Cross/Red Crescent Movement, international and local non-governmental organizations (NGOs), private entities, governments, and civil society – all vying for scarce resources from a limited pool of fatigued donors (Weiss 2013). Existing theoretical approaches on inter-organizational competition suggest that, under conditions of density and resource scarcity, competing actors are encouraged to pursue niche specialization as an avenue to secure organizational survival. This logic underpins the UN’s Humanitarian Cluster Approach, where each UN organization, agency, or programme with a humanitarian role is assigned to a specific sector of the response, taking on coordination, advocacy, and provider-of-last-resort responsibilities. While the Cluster Approach was intended to reduce duplication and establish a clear division of labour among UN entities, in practice, humanitarian workers and external observers lament the persistence of siloed thinking and competition among UN organizations.